Motives for Actual Open Market Share Repurchases – the UK Evidence - Xin, Jing (2017)
In this study, motives behind the actual open market share repurchases are examined using the data of the UK-domiciled listed companies observed from the year 2009 to 2016. These firms are the components of FTSE350 by August 2017, excluding those engage in the financial and insurance sector. A random-effect panel logistic regression is applied on total sample firms to estimate the probability of a firm to make actual open market share repurchase. Furthermore, a two-way fixed-effect panel regression is applied on repurchasers (repurchase own shares at least once during the observation period) to find the factors changing the volume of shares repurchased over the years. Overall, the evidence lends support to the assumed motives including capital structure optimisation, information signalling and distribution of excess cash. However, these motives hypothesised for the share repurchase have different degree of impacts on companies’ decisions to launch an actual open market share repurchase as a non- repurchaser before or to allocate resource over the years to buy back own shares as a repurchaser. In addition, share repurchases appear sensitive to the macroeconomics.